SISTEM PERHITUNGAN BIAYA BERDASARKAN JOB ORDER COSTING, PROCESS COSTING, ACTIVITY BASE COSTING, ACTIVITY BASE MANAGEMENT - Wiwi Idawati (Universitas Bunda Mulia, 2017)
Sharp world level competition caused investors direct planting their funds into efforts that enabled large in generating profits, while businesses that are capable of producing large profits will soon attract many investors to infuse capital into the business. Activities to service orders and presents cost information for management, cost accounting procedures in the method of cost of goods orders include organizational forms, records and reports that are coordinated in order to carry out the Activity Based Costing provides information about activities and resources needed to carry out such activities. In some ways, process costing have in common and the difference with the job order costing. The main purpose of these systems is imposes cost of raw materials , labor and overhead into products and give mechanism tally cost per unit .Keywords: Job Order Costing, Process Costing, Activity Base Costing, Activity Base Management.